(untitled) - Frédéric, Louis (Cambridge, Mass., 2002)
"Knowing Japan and the Japanese better," Louis Frederic states in the introduction to this encyclopedia, "is one of the necessities of modern life." The Japanese have a profound knowledge of every aspect and detail of Western societies. Unfortunately, we in the West cannot say the same about our knowledge of Japan. We tend to see Japan through a veil of exoticism, as a land of ancient customs and exquisite arts; or we view it as a powerful contributor to the global economy, the source of cutting-edge electronics and innovative management techniques. To go beyond these cliches, we must begin to see how apparently contradictory aspects of modern Japanese culture spring from the country's evolution through more than two millennia of history. This richly detailed yet concise encyclopedia is a guide to the full range of Japanese history and civilization, from the dawn of its prehistory to today, providing clear and accessible information on society and institutions, commerce and industry, sciences, sports, and politics, with particular emphasis on religion, material culture, and the arts. The volume is enhanced by maps and illustrations, along with a detailed chronology of more than 2,000 years of Japanese history and a comprehensive bibliography. Cross-references and an index help the reader trace themes from one article to the next. Japan Encyclopedia will be an indispensable one-volume reference for students, scholars, travelers, journalists, and anyone who wishes to learn more about the past and present of this great world civilization.
Keywords: Japan,Nhật Bản; Civilization,Nền văn minh